Secondary Metabolites from Cissampelos, A Possible Source for New Leads with Anti-Inflammatory Activity - F. Alves, Mateus; T.Scotti, Marcus; Scotti, Luciana; Jaime Bezerra Mendonça, Francisco; M. B. Filho, Jose; A L. de Melo, Sílvia; G. dos Santos, Sócrates; de F.F.M. Diniz, Margareth (Current Medicinal Chemistry, 2017)
The genus Cissampelos comprises of 21 species which have a wide global distribution and various pharmacological activities such as analgesic and antipyretic, antiinflammatory, anti-allergic, bronchodilation, and immunomodulation among others. Several compounds, mainly alkaloids with differing biological activities have been isolated from this genus. We will highlight antipyretic activities, anti-inflammatory, antiallergic, bronchodilatory, and immunomodulatory activities. In addition, we applied ligand-based-virtual screening associated with structure-based-virtual screening of a small dataset of 63 secondary metabolites from the Cissampelos genus of an in-house data bank, in order to select compounds with potential anti-inflammatory activity. Affinities were observed for hayatine (26), isochondrondendrine (30), pelosine (52), sepeerine (59), and warifteine (63) to the inhibiting enzymes MAPK p38 alpha, PKC beta, PKC theta and PKC zeta. The cissampeloflavone compound (8) alone showed no potential inhibitory activity for PKC zeta, or affinity for the PKC alpha. The compounds can be used as starting points for further studies on structures with potential anti-inflammatory activity.
Keywords: anti-inflammatory activity